OpenMp solvers for parallel finite element and meshless analyses. Issue 1 (2014) - S.H. Ju
<x xml:space="preserve"> Abstract </x> Purpose – This paper develops C++ and Fortran‐90 solvers to establish parallel solution procedures in a finite element or meshless analysis program using shared memory computers. The paper aims to discuss these issues. Design/methodology/approach – The stiffness matrix can be symmetrical or unsymmetrical, and the solution schemes include sky‐line Cholesky and parallel preconditioned conjugate gradient‐like methods. Findings – By using the features of C++ or Fortran‐90, the stiffness matrix and its auxiliary arrays can be encapsulated into a class or module as private arrays. This class or module will handle how to allocate, renumber, assemble, parallelize and solve these complicated arrays automatically. Practical implications – The source codes can be obtained online at http//myweb.ncku.edu.tw/∼juju. The major advantage of the scheme is that it is simple and systematic, so an efficient parallel finite element or meshless program can be established easily. Originality/value – With the minimum requirement of computer memory, an object‐oriented C++ class and a Fortran‐90 module were established to allocate, renumber, assemble, parallel, and solve the global stiffness matrix, so that the programmer does not need to handle them directly.